Reindeer husbandry vs. wind energy: analysis of the Pauträsk and Norrbäck court decisions in Sweden - Cambou, Dorothée; Sandström, Per; Skarin, Anna; Borg, Emma (2022)
In 2019, the Land and Environmental Court of Appeal, Sweden’s highest court in environmental matters, authorized the establishment of two wind energy projects in the Norrbäck and Pauträsk areas on the winter grazing lands of Vapsten sameby in northern Sweden. These decisions overturned previous court rulings that rejected the two wind energy projects due to the expected impacts on nature and cultural values, and because the projects were seen to harm the interests of reindeer husbandry. In the analysis of these two legal cases, we seek to understand and explain the judicial conflicts between Sámi samebyar and wind energy developers. Based on the interpretation of the court decisions, we focus on the main features of the courts’ reasoning and examine how the courts have assessed the impact of wind turbines on reindeer husbandry. This chapter thus explains the main factors that have influenced and limited the court decisions and also concludes that these court decisions have failed to guarantee the right of the Sámi Indigenous people to practice sustainable reindeer husbandry in Sweden.